2001
DOI: 10.1029/2001jd000805
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between synoptic‐scale transport and interannual variability of inorganic cations in surface snow at Summit, Greenland: 1992–1996

Abstract: Abstract. To fully utilize the long-term chemical records retrieved from central Greenland ice species in the records need to be better understood. This research examines associations between the variability of surface snow inorganic cation chemistry at Summit, Greenland (collected during 1992-1996 summer field seasons) and changes in air mass transport pathways and source regions, as well as variations in aerosol source strength. Transport patterns and source regions are determined through 10-day isentropic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“… Dibb et al [1996] tracked the transport of a biomass burning plume from the Hudson Bay lowlands region of Canada to Summit, Greenland. Slater et al [2001] showed that at least 50% of the air masses transported to Summit during May/June of 1992–1996 had origins in the North American sector, which included regions down to 40°N latitude. Their evidence included increased soil dust aerosols (as represented by Ca and Mg soluble ions) during 1995 that could only have come from snow‐free areas south of 60°N latitude.…”
Section: Discussionmentioning
confidence: 99%
“… Dibb et al [1996] tracked the transport of a biomass burning plume from the Hudson Bay lowlands region of Canada to Summit, Greenland. Slater et al [2001] showed that at least 50% of the air masses transported to Summit during May/June of 1992–1996 had origins in the North American sector, which included regions down to 40°N latitude. Their evidence included increased soil dust aerosols (as represented by Ca and Mg soluble ions) during 1995 that could only have come from snow‐free areas south of 60°N latitude.…”
Section: Discussionmentioning
confidence: 99%
“… Owega et al [2004] and Hudson et al [2004] reported that K can be one of the specific markers of forest fire aerosols from midlatitude and high‐latitude regions. Slater et al [2001] showed that an increased level of K + in surface snow at Greenland was concurrent with an increased forest fire activity in North America. Although increases in K + concentration in aerosols during 21 and 24 May and 5–10 June events are recognizable (Figure 3c) in our measurements, the difference in value between smoke and nonsmoke days (e.g., 0.42 μ g m −3 on 21 May versus 0.09 μ g m −3 on 1 May) was not as prominent as that of BC (1948 ng m −3 versus 41 ng m −3 for the corresponding days).…”
Section: Resultsmentioning
confidence: 99%
“…5c). for 1996, Slater and others (2001) found that >20% of 10 day trajectory origins were located in theYukon and Siberia.…”
Section: Resultsmentioning
confidence: 99%
“…Dibb and others (1996) used three-dimensional trajectories to investigate chemical signatures associated with the transport of biomass-burning emissions from North America. More recently, Slater and others’ (2001) analysis of three-dimensional back trajectories again revealed the importance of transport from North America. Although Slater and others’ work considered three-dimensional transport to Summit, the vertical component of transport was not considered in a comprehensive or systematic manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation